NILAI-NILAI FEMINISME DALAM NOVEL MERRY RIANA: MIMPI SEJUTA DOLAR KARYA ALBHERTIENE ENDAH* (Feminism Values in Novel â€œMerry Riana: Mimpi Sejuta Dollarâ€ by Albhertiene Endah) - Rachmawati, Dian Erika; Ravitasari, Rizki Agung (ALAYASASTRA, 2019)
This research is based on the development of feminism values in the community. In a patriarchal environment, women have a low position compared to men. Women are subordinated in various fields of life, such as in the fields of education, social affairs and economics. This study aims to describe the values of feminism contained in the novel ?Merry Riana: Mimpi Sejuta Dollar? by Alberthiene Endah. This type of research is a qualitative descriptive study with a feminist literary criticism approach. The research method used is content analysis with data collection techniques read and record. The data source in this study is the novel ?Merry Riana: Mimpi Sejuta Dollar? by Alberthiene Endah. Based on the results of the research, in the novel ?Merry Riana: Mimpi Sejuta Dollar? by Alberthiene Endah there are values of feminism which include: (a) the value of feminism in education, (b) the value of feminism in the social field, and (c) the value of feminism in the economic. Keywords: values of feminism, the study of feminism, novels.